Relationship between Eustachian Tube Dimensions and Middle Ear Cholesteatoma - Gülüstan, Filiz; Güneş, Selçuk; Yıldız, Ömer; Mine Yazıcı, Zahide; Akif Abakay, Mehmet; İnci, Ercan; Sayın, İbrahim (ENT Updates, 2020)
Objective: To compare intact and diseased ears for Eustachian tube (ET) length and width in patients with unilateral chronic otitis media (COM), and to assess the relationship between cholesteatoma spread, stapes erosion, lateral semicircular canal (LSCC) fistula and ET width and length retrospectively. Methods: Subjects with unilateral COM (122 subjects with 244 ears) who underwent surgery for cholesteatoma were evaluated retrospectively for this study. The width of the distal orifice of the bony segment and the length of the bony segment of the ET for both the diseased and healthy ear were measured. Subjects’ healthy and diseased ears were compared for ET length and width. The diseased sides were compared to assess the relationship between ET dimensions and cholesteatoma spread, stapes erosion and LSCC fistula. Results: The mean ET length and width in healthy and diseased ears was 11.38±1.7 and 1.43±0.37 mm, and 10.99±1.6 and 1.27±0.35 mm, respectively; the difference was statistically significant (p<0.001). No significant differences were found in terms of ET length and width between the subjects with and without stapes erosion and LSCC fistula (p=0.765, p=0.573, and p=0.436, p=0.790, respectively). No significant relation was found between cholesteatoma spread and ET length and width (p=0.647). Conclusion: ET dysfunction is frequently associated with COM. Chronic otitis media with cholesteatoma is significantly related to ET length and width. Measurement of ET length and width in CT scans is a basic method that can be used in clinical practice.